2022
DOI: 10.1002/tax.12688
|View full text |Cite
|
Sign up to set email alerts
|

Intergeneric relationships within the tribe Alsineae (Caryophyllaceae) as inferred from nrDNA ITS and cpDNArps16 sequences: A step toward a phylogenetically based generic system

Abstract: The tribe Alsineae is a large monophyletic group in the family Caryophyllaceae especially found across Eurasia and the Americas, but with a center of diversity in the Mediterranean region. Several previous molecular phylogenetic studies have focused on the delimitation of genera and tribes of Caryophyllaceae, especially the subfamily Alsinoideae or the tribe Alsineae in a broader sense than now recognized. However, there are still many open questions regarding the subdivision of the tribe and genus delimitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 47 publications
2
18
3
Order By: Relevance
“…GenBank accession numbers nrITS trnL-F matK rps16 rcbL A. Sequences used to generate Caryophyllaceae tree (Fig. 3A) length of the petals) (1), deeply lobed (longer than 1/2 the length of the petals) (2); (b) the number of seeds in a capsule is 1-3 (0), 4-6 (1), more than 6 (2) Arabi et al 2022).…”
Section: Taxonmentioning
confidence: 99%
See 1 more Smart Citation
“…GenBank accession numbers nrITS trnL-F matK rps16 rcbL A. Sequences used to generate Caryophyllaceae tree (Fig. 3A) length of the petals) (1), deeply lobed (longer than 1/2 the length of the petals) (2); (b) the number of seeds in a capsule is 1-3 (0), 4-6 (1), more than 6 (2) Arabi et al 2022).…”
Section: Taxonmentioning
confidence: 99%
“…was proposed based on morphological studies (Pusalkar and Srivastava 2016). The molecular studies also indicated that Stellaria monosperma was far from the core Stellaria and nested within Schizotechium (Greenberg and Donoghue 2011;Sharples and Tripp 2019;Arabi et al 2022). Although Stellaria ovatifolia was hypothesized to be part of Schizotechium (Pusalkar and Srivastava 2016), it has never been sampled and has at times been placed in Brachystemma, Schizotechium, or Stellaria, and its phylogenetic position is still pending.…”
Section: Introductionmentioning
confidence: 99%
“…TreeGraph 2.15.0-887 beta (Stöver & Müller 2010) was used to visualize and annotate the trees based on the Bayesian majority rule consensus, and depicting confidence values for nodes from all three tree inference methods. Scleranthus annuus L. was selected to root the trees to a relatively distant taxon outside the Alsineae and Arenarieae tribes as its putative sister (Arabi & al. 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The genus Plettkea , which was not sampled by Arabi & al. (2022), is a further Andean taxon of the Alsineae that forms small cushions. However, Sharples & Tripp (2019) had already included one of its members, Plettkea tetrasticha Mattf., in their RAD analysis of the genus Stellaria along with nine South American species of Stellaria (from the ‘Petiolares’ clade), and depicted it nested within Stellaria .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation